Reason in the Context of Man’s Vocation in Plato, Aristotle, and Descartes - Kešeljević, Luka M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper addresses the problem of reason in antiquity (Plato and Aristotle) and in modernity (Descartes). The first section introduces the question of reason as man’s vocation; the second section deals with the question of rationality in Plato and Aristotle; the third section discusses the problem of reason in modern philosophy with Descartes, while the final section considers a possible step forward from modern metaphysics to anthropology. The discussion of philosophical anthropology’s foundations permeates throughout the entire paper.